Enhanced broadband low-frequency performance of negative Poisson’s ratio metamaterials with added mass - Yuxin Liu; Shuihai Dou; Yanping Du; Runze Liang; Shengying Yue; Liuxian Zhao; Feng Liu; Zhaoyong Sun; Jun Yang (Scientific Reports)
Abstract In this work, we propose a negative Poisson’s ratio metamaterial with added mass (NPM). Introducing added mass induces the emergence of new bandgaps, effectively reducing the bandgap frequency and widening its width. Simulation results show that added mass can generate new low-frequency bandgaps. Vibration transmission spectra of the structure are measured through vibration experiments, which closely matched the bandgaps, confirming the vibration reduction function of the structure. In addition, the energy absorption performance of the NPMs under quasi-static compression is experimentally tested. The results show that although the introduction of added mass affects the energy absorption effect to a certain extent, arranging the metamaterial units into a gradient structure based on the mass gradient significantly enhances the vibration isolation and energy absorption effects. This study presents a pioneering methodology for the development of integrated metamaterials capable of accommodating multiple functionalities.